Optimal. Leaf size=17 \[ \log \left (\frac {x \log (x)}{1-e^2+3 x}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.26, antiderivative size = 19, normalized size of antiderivative = 1.12, number of steps used = 9, number of rules used = 7, integrand size = 37, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.189, Rules used = {6, 1593, 6742, 36, 31, 29, 2302} \begin {gather*} \log (x)-\log \left (3 x-e^2+1\right )+\log (\log (x)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 6
Rule 29
Rule 31
Rule 36
Rule 1593
Rule 2302
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-1+e^2-3 x+\left (-1+e^2\right ) \log (x)}{\left (\left (-1+e^2\right ) x-3 x^2\right ) \log (x)} \, dx\\ &=\int \frac {-1+e^2-3 x+\left (-1+e^2\right ) \log (x)}{\left (-1+e^2-3 x\right ) x \log (x)} \, dx\\ &=\int \left (\frac {-1+e^2}{\left (-1+e^2-3 x\right ) x}+\frac {1}{x \log (x)}\right ) \, dx\\ &=\left (-1+e^2\right ) \int \frac {1}{\left (-1+e^2-3 x\right ) x} \, dx+\int \frac {1}{x \log (x)} \, dx\\ &=3 \int \frac {1}{-1+e^2-3 x} \, dx+\int \frac {1}{x} \, dx+\operatorname {Subst}\left (\int \frac {1}{x} \, dx,x,\log (x)\right )\\ &=\log (x)-\log \left (1-e^2+3 x\right )+\log (\log (x))\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.06, size = 19, normalized size = 1.12 \begin {gather*} \log (x)-\log \left (1-e^2+3 x\right )+\log (\log (x)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.60, size = 18, normalized size = 1.06 \begin {gather*} -\log \left (3 \, x - e^{2} + 1\right ) + \log \relax (x) + \log \left (\log \relax (x)\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.15, size = 18, normalized size = 1.06 \begin {gather*} -\log \left (3 \, x - e^{2} + 1\right ) + \log \relax (x) + \log \left (\log \relax (x)\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.38, size = 17, normalized size = 1.00
method | result | size |
norman | \(\ln \relax (x )-\ln \left ({\mathrm e}^{2}-1-3 x \right )+\ln \left (\ln \relax (x )\right )\) | \(17\) |
risch | \(-\ln \left (1+3 x -{\mathrm e}^{2}\right )+\ln \relax (x )+\ln \left (\ln \relax (x )\right )\) | \(19\) |
default | \(\ln \left (\ln \relax (x )\right )-\frac {{\mathrm e}^{2} \ln \left (1+3 x -{\mathrm e}^{2}\right )}{{\mathrm e}^{2}-1}+\frac {{\mathrm e}^{2} \ln \relax (x )}{{\mathrm e}^{2}-1}+\frac {\ln \left (1+3 x -{\mathrm e}^{2}\right )}{{\mathrm e}^{2}-1}-\frac {\ln \relax (x )}{{\mathrm e}^{2}-1}\) | \(63\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.38, size = 18, normalized size = 1.06 \begin {gather*} -\log \left (3 \, x - e^{2} + 1\right ) + \log \relax (x) + \log \left (\log \relax (x)\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.56, size = 18, normalized size = 1.06 \begin {gather*} \ln \left (\ln \relax (x)\right )-\ln \left (3\,x-{\mathrm {e}}^2+1\right )+\ln \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [B] time = 0.33, size = 141, normalized size = 8.29 \begin {gather*} \left (1 - e^{2}\right ) \left (\frac {\log {\left (x - \frac {e^{4}}{6 \left (-1 + e\right ) \left (1 + e\right )} - \frac {e^{2}}{6} - \frac {1}{6 \left (-1 + e\right ) \left (1 + e\right )} + \frac {1}{6} + \frac {e^{2}}{3 \left (-1 + e\right ) \left (1 + e\right )} \right )}}{\left (-1 + e\right ) \left (1 + e\right )} - \frac {\log {\left (x - \frac {e^{2}}{6} - \frac {e^{2}}{3 \left (-1 + e\right ) \left (1 + e\right )} + \frac {1}{6 \left (-1 + e\right ) \left (1 + e\right )} + \frac {1}{6} + \frac {e^{4}}{6 \left (-1 + e\right ) \left (1 + e\right )} \right )}}{\left (-1 + e\right ) \left (1 + e\right )}\right ) + \log {\left (\log {\relax (x )} \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________